Diagnosis of voice disorders using band energy spectrum in wavelet domain - Murugesa Pandiyan, Paulraj, Prof. Madya Dr,; Sazali, Yaacob, Prof. Dr.; Muthusamy, Hariharan, Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Universiti Malaysia Perlis (UniMAP), 8th - 10th March 2008 at Putra Brasmana, Perlis, Malaysia.